2015
DOI: 10.1016/j.ecolmodel.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Improved global simulations of gross primary product based on a new definition of water stress factor and a separate treatment of C3 and C4 plants

Abstract: A B S T R A C TAccurate simulation of terrestrial gross primary production (GPP), the largest global carbon flux, benefits our understanding of carbon cycle and its source of variation. This paper presents a novel light use efficiency-based GPP model called the terrestrial ecosystem carbon flux model (TEC) driven by MODIS FPAR and climate data coupled with a precipitation-driven evapotranspiration (E) model (Yan et al., 2012). TEC incorporated a new water stress factor, defined as the ratio of actual E to Prie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 110 publications
4
44
0
Order By: Relevance
“…A vapor pressure deficit (VPD)‐based stressor was a widely criticized problem in the MOD17 algorithm and previous studies suggested that a soil moisture based water stress should be included in the algorithm [ Kanniah et al ., ; Leuning et al ., ; Mu et al ., ; Pan et al ., ; Yan et al ., ]. However, analyses have shown that models that do not directly consider soil moisture can still capture the impacts of drought on GPP [ He et al ., ; Wagle et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…A vapor pressure deficit (VPD)‐based stressor was a widely criticized problem in the MOD17 algorithm and previous studies suggested that a soil moisture based water stress should be included in the algorithm [ Kanniah et al ., ; Leuning et al ., ; Mu et al ., ; Pan et al ., ; Yan et al ., ]. However, analyses have shown that models that do not directly consider soil moisture can still capture the impacts of drought on GPP [ He et al ., ; Wagle et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Modeling evapotranspiration (ET), the combined loss of water from soil through evaporation and from vegetation through transpiration, has many applications in agricultural management [1,2], carbon sequestration [3,4], climate modeling [5], drought monitoring [6], energy security [7], hydrological modeling [8], irrigation scheduling [9], and watershed development [10,11]. Various models and techniques are used for accurately estimating ET at field to global scales.…”
Section: Introductionmentioning
confidence: 99%
“…As soil moisture and VPD directly affect photosynthesis, more GPP models explicitly consider the effect of soil moisture as well as temperature. The effect of water stress on ecosystem photosynthesis may be the most uncertain factor in current LUE GPP models (Yan et al, 2015). Also, model validation needs flux measurements from more sites encompassing various ecosystem types to test the applicability and accuracy, which can lay foundation for the carbon flux upscaling.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to validation against measured GPP, the capacity of the CI-LUE model to simulate GPP was compared with GPP simulated by MOD17 model driven by in situ meteorological measurements (GPP _17 ), MODIS GPP products (GPP _MOD ), the VPM algorithm (Xiao et al, 2004), and the TEC model proposed by Yan et al (2015). The VPM model employed climate data, MODIS Land Surface Water Index (LSWI) and EVI to calculate 8-day GPP.…”
Section: Model Validation and Comparisonsmentioning
confidence: 99%